2019
DOI: 10.1016/j.jad.2019.04.084
|View full text |Cite
|
Sign up to set email alerts
|

The role of familial risk, parental psychopathology, and stress for first-onset depression during adolescence

Abstract: Background: Adolescence represents a critical developmental period during which the initial onset of depression emerges. Family risk for depression is a salient risk factor for the initial onset of Major Depressive Disorder (MDD). We examined the effects of familial risk, stress, and behavior on the risk of developing first-onset depression.Methods: Adolescents aged 12 to 15 with high (n = 166) or low (n = 159) familial risk for depression were assessed annually for up to five years. Stress was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
0
11
0
2
Order By: Relevance
“…The five major neuropsychiatric disorders are bipolar disorder (BP), MDD, ADHD, Schizophrenia (SCZ), and PTSD; many of these disorders have overlapping symptomatology or high comorbidity rates making it challenging to make a definite diagnosis. Each one of the neuropsychiatric disorders has been extensively linked to genetics in that having a parent or sibling with the neuropsychiatric disorders increases the risk of development of that disorder (Picchioni et al ; Mustafin et al ; Stapp et al ; Isaksson et al ; Elsayed et al ). Similar to the role of NE and DβH in substance abuse, DβH involvement in neuropsychiatric disorders is linked to alterations in plasma/sera DβH activity (Table ), while direct pharmaceutical interventions in NE signaling (antagonist/agonist) or DβH (inhibitor) are frequency employed in treatment (Maletic et al ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…The five major neuropsychiatric disorders are bipolar disorder (BP), MDD, ADHD, Schizophrenia (SCZ), and PTSD; many of these disorders have overlapping symptomatology or high comorbidity rates making it challenging to make a definite diagnosis. Each one of the neuropsychiatric disorders has been extensively linked to genetics in that having a parent or sibling with the neuropsychiatric disorders increases the risk of development of that disorder (Picchioni et al ; Mustafin et al ; Stapp et al ; Isaksson et al ; Elsayed et al ). Similar to the role of NE and DβH in substance abuse, DβH involvement in neuropsychiatric disorders is linked to alterations in plasma/sera DβH activity (Table ), while direct pharmaceutical interventions in NE signaling (antagonist/agonist) or DβH (inhibitor) are frequency employed in treatment (Maletic et al ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…Previous epidemiological and clinical researches have indicated that adolescent depression has numerous individual, family and social factors. Reported risk factors for adolescent depression include being female, anxious, offspring of depressed parents, and being exposed to stress or trauma [2][3][4]. However, many of the known contributing factors have been described in the western context.…”
Section: Introductionmentioning
confidence: 99%
“…12 Usia ini merupakan periode tumbuh kembang seorang individu yang sensitif terhadap stress dan depresi. 13 Responden penelitian ini merupakan mahasiswa yang terpapar dengan sejumlah stressor fisiologis dan psikologis. Sejumlah emosi negatif dapat muncul sebagai dampak respon terhadap stress.…”
Section: Pembahasanunclassified